Integrating Wind Energy in Desalination: A Water-Food-Energy Nexus Approach in Dakhla, Morocco - Elhabnouny Mohammed; Ouadrhiri Salma; Menchafou Youssef; Zejli Driss; Saad Aouatif (E3S Web of Conferences)
This study explores the wind energy potential for a wind-powered desalination project in Dakhla, Morocco, by analyzing two models: the Weibull distribution and the WAsP model. Over two years of wind data were processed to estimate energy production, with the Weibull model offering a baseline and the WAsP model refining predictions with site-specific variables. The project, a Public-Private Partnership (PPP), serves 219 agricultural estates over 5200 hectares and ensures potable water for Dakhla’s residents. The PPP framework promotes financial sustainability, with funding shared between public and private stakeholders, ensuring long-term viability in addressing the region’s water-energy needs.